Impact of Moisture Variations on NH₃ and H₂S Emissions During Municipal Solid Waste Drying Using Waste Motor Oil Interceptor System: A Case from Denpasar, Bali - Prakasa, I Made Panji Tirta; Andrayuga, I Wayan; Sutasoma, I Wayan Gde; Putra, Anak Agung Adi Wiryya (Journal of Engineering and Science, 2025)
Municipal solid waste (MSW) production continues to rise globally, especially in developing countries such as Indonesia, creating significant environmental challenges. This study investigates the impact of moisture content (MC) variation on ammonia (NH₃) and hydrogen sulfide (H₂S) emissions during the MSW drying process, and evaluates the effectiveness of a gas capture system using waste motor oil (WMO). Laboratory-scale experiments were conducted at Universitas Pendidikan Nasional in collaboration with Universitas Udayana, using MSW samples conditioned at five moisture levels: 50%, 40%, 30%, 20%, and 10%. Emissions were measured before and after treatment with the WMO-based interceptor system. The results showed that the highest gas emissions occurred at 50% MC, with corresponding reduction efficiencies of 73.9% (50% MC), 70.0% (40%), 72.1% (30%), 55.9% (20%), and 5.4% (10%). Higher MC was associated with increased anaerobic microbial activity and organic matter decomposition, leading to elevated NH₃ and H₂S generation. The WMO system demonstrated strong gas adsorption performance, particularly at moderate to high MC levels. These findings suggest that controlling MC and applying low-cost WMO-based gas interception can significantly reduce emissions in waste drying processes. This approach holds promise for improving air quality in urban waste management systems, especially in resource-limited settings.